Stress responses in free ranging brown bears (Ursus arctos) in eastern Türkiye - Naderi, Morteza; Palme, Rupert; Yarnell, Kelly; Çoban, Emrah; Çoban, Ayşegül Karaahmetoğlu; Kusak, Josip; Şekercioğlu, Çağan H. (Frontiers in Veterinary Science, 2025)
Brown bears (Ursus arctos) are a keystone species vital for maintaining ecological balance in northeastern Türkiye. However, increasing human activities—such as logging, agriculture, and recreation—pose significant threats to their conservation. It is therefore crucial to assess how these specific anthropogenic pressures influence bears’ physiological stress responses to inform effective conservation strategies. Our hypothesis that increased human activity would correlate with elevated stress markers in bears was tested by collecting blood serum samples from 50 free-ranging bears during live capture. Blood cortisol levels and fecal cortisol metabolites were measured to assess stress responses. We also employed camera trap surveys to quantify human activity levels across different habitat patches, calculating a Relative Abundance Index (RAI). Statistical analyses, including correlation and regression models, were used to assess relationships between cortisol measures, habitat features, and human presence. The study revealed an inverse correlation between bear mass and blood cortisol levels and a significant relationship between fecal cortisol metabolites and human presence, as quantified through camera trap data. These findings highlight the significant impact of human disturbances on bear stress physiology, the urgent need for effective conservation measures to minimize human-wildlife conflicts and support the long-term viability of bear populations in Türkiye. These findings highlight that fecal cortisol metabolites serve as reliable, non-invasive indicators of stress in free ranging brown bears, enabling large-scale monitoring to identify habitat disturbance hotspots, assess the effectiveness of protected areas, and inform targeted management actions to minimize human-wildlife conflicts and enhance habitat quality.